1993
DOI: 10.1128/mcb.13.4.2411
|View full text |Cite
|
Sign up to set email alerts
|

Alternative poly(A) site utilization during adenovirus infection coincides with a decrease in the activity of a poly(A) site processing factor.

Abstract: The recognition and processing of a pre-mRNA to create a poly(A) addition site, a necessary step in mRNA biogenesis, can also be a regulatory event in instances in which the frequency of use of a poly(A) site varies. One such case is found during the course of an adenovirus infection. Five poly(A) sites are utilized within the major late transcription unit to produce more than 20 distinct mRNAs during the late phase of infection. The proximal half of the major late transcription unit is also expressed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…The mRNA 39-end-processing reaction occurs in two tightly coupled steps: the cleavage of the pre-mRNA at the poly(A) site, followed by the addition of a poly(A) tail to the newly generated 39 end (reviewed in Wahle & Rüegsegger, 1999;Zhao et al+, 1999)+ In mammals, the poly(A) site is located between the upstream consensus poly(A) signal AAUAAA and a downstream variable GU-or U-rich sequence+ These sequences interact with multiprotein complexes: the cleavage and polyadenylation specificity factor (CPSF) and the cleavage stimulation factor (CstF), respectively+ CPSF consists of four subunits and binds the AAUAAA through its 160-kDa (160K) and its 30-kDa (30K) subunits, whereas CstF, which consists of three subunits, 77 kDa (77K), 64 kDa (64K), and 50 kDa (50K), binds the GUrich downstream motif via its 64K subunit+ CPSF and CstF bind cooperatively to RNA, promoting the formation of a cleavage complex on the pre-mRNA, which also contains the two cleavage factors CFIm and CFIIm, and the poly(A) polymerase (PAP)+ Cooperativity of RNA binding by CPSF-CstF results, at least in part, from an interaction between the 160K subunit of CPSF and the 77K subunit of CstF (Murthy & Manley, 1995)+ The 77K protein also bridges the other two subunits (64K and 50K) of CstF (Takagaki & Manley, 1994), it interacts with itself (Simonelig et al+, 1996;Takagaki & Manley, 2000), and it binds to the CTD of RNA polymerase II (McCracken et al+, 1997), thus contributing to the cou-pling between transcription and 39-end processing (reviewed in Bentley, 1999)+ CstF is thought to play an important role in the regulation of poly(A) site selection+ Indeed, poly(A) site efficiency is defined in vitro by the stability of the cleavage complex on the pre-mRNA which, in turn, depends on affinity of CstF for the downstream variable GU-rich elements (Weiss et al+, 1991)+ Consistent with this, several studies have correlated shifts in the choice of poly(A) sites with variations in the level or activity of the 64K subunit of CstF (Mann et al+, 1993;EdwaldsGilbert & Milcarek, 1995;Takagaki et al+, 1996;Takagaki & Manley, 1998)+…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The mRNA 39-end-processing reaction occurs in two tightly coupled steps: the cleavage of the pre-mRNA at the poly(A) site, followed by the addition of a poly(A) tail to the newly generated 39 end (reviewed in Wahle & Rüegsegger, 1999;Zhao et al+, 1999)+ In mammals, the poly(A) site is located between the upstream consensus poly(A) signal AAUAAA and a downstream variable GU-or U-rich sequence+ These sequences interact with multiprotein complexes: the cleavage and polyadenylation specificity factor (CPSF) and the cleavage stimulation factor (CstF), respectively+ CPSF consists of four subunits and binds the AAUAAA through its 160-kDa (160K) and its 30-kDa (30K) subunits, whereas CstF, which consists of three subunits, 77 kDa (77K), 64 kDa (64K), and 50 kDa (50K), binds the GUrich downstream motif via its 64K subunit+ CPSF and CstF bind cooperatively to RNA, promoting the formation of a cleavage complex on the pre-mRNA, which also contains the two cleavage factors CFIm and CFIIm, and the poly(A) polymerase (PAP)+ Cooperativity of RNA binding by CPSF-CstF results, at least in part, from an interaction between the 160K subunit of CPSF and the 77K subunit of CstF (Murthy & Manley, 1995)+ The 77K protein also bridges the other two subunits (64K and 50K) of CstF (Takagaki & Manley, 1994), it interacts with itself (Simonelig et al+, 1996;Takagaki & Manley, 2000), and it binds to the CTD of RNA polymerase II (McCracken et al+, 1997), thus contributing to the cou-pling between transcription and 39-end processing (reviewed in Bentley, 1999)+ CstF is thought to play an important role in the regulation of poly(A) site selection+ Indeed, poly(A) site efficiency is defined in vitro by the stability of the cleavage complex on the pre-mRNA which, in turn, depends on affinity of CstF for the downstream variable GU-rich elements (Weiss et al+, 1991)+ Consistent with this, several studies have correlated shifts in the choice of poly(A) sites with variations in the level or activity of the 64K subunit of CstF (Mann et al+, 1993;EdwaldsGilbert & Milcarek, 1995;Takagaki et al+, 1996;Takagaki & Manley, 1998)+…”
Section: Introductionmentioning
confidence: 68%
“…Model for tissue-specific su(f) autoregulation+ The Su(f) protein regulates its own level by promoting the utilization of poly(A) site in su(f) intron 4, which leads to the formation of a truncated transcript+ In dividing tissues, this autoregulation is weak, possibly because of the lack or the low amount of another component essential for Su(f) activity on the su(f) intronic poly(A) site+ This allows Su(f) accumulation+ In nondividing tissues, su(f) autoregulation is strong, possibly as a result of a high level of the protein required for efficient Su(f) activity on the su(f) intronic poly(A) site+ This results in the synthesis of a very low level of Su(f) protein+ type expression pattern of the P[su(f)-lacZ]G reporter is restored in the su(f) ts67g mutant+ Therefore, in that experiment, accumulation of the Su(f)-b-galactosidase protein is repressed in nondividing tissues but not in dividing tissues although the Su(f) protein is present at the same level in both tissues+ This suggests that this repression in nondividing tissues depends on another protein that stimulates utilization of the poly(A) site in intron 4 (Fig+ 5)+ This protein would induce a modification of Su(f) activity either via a direct posttranslational modification of Su(f) or by interacting with Su(f)+ Such a Su(f)-interacting protein could be a specific protein or a component of the general 39-end processing machinery+ An obvious candidate is the 64K subunit of CstF known to interact with the 77K subunit in human (Takagaki & Manley, 1994)+ Variations in the level of this 64K subunit contribute to the shift in poly(A) site selection in the immunoglobulin M heavy-chain locus, during B cell differentiation (Takagaki et al+, 1996;Takagaki & Manley, 1998)+ Autoregulation of su(f) appears to be conserved in another Drosophila species, D. virilis , as the structure of the su(f) gene as well as sequences downstream of the intronic poly(A) site, including the GU-rich motif, are conserved in this species+ Interestingly, such autoregulation has been proposed to occur for the yeast homolog of su(f), the RNA14 gene (Mandart, 1998)+ The RNA14 gene also produces truncated RNAs, whose accumulation requires wildtype RNA14 function+ The fact that autoregulation of this gene is conserved from yeast to Drosophila suggests that the level of this protein must be tightly regulated+ Consistent with this, overexpression of su(f) in Drosophila using the UAS/Gal4 system can lead to lethality+ In mammals, several examples document the fact that variations in the general cleavage factor CstF participate in the regulation of poly(A) site choice+ In most cases, the 64K subunit of CstF has been found to be responsible for these variations+ Variations in the activity of 64K have been reported to occur during the shift in poly(A) site choice in adenovirus (Mann et al+, 1993)+ An increase in the 64K level participates in the switch of poly(A) site utilization in the immunoglobulin M heavy-chain locus during B cell maturation (Takagaki et al+, 1996;Takagaki & Manley, 1998)+ The 64K subunit level has also been shown to increase in cultured cells induced to proliferate (Martincic et al+, 1998), and recently a new form of the 64K protein has been described in mouse (Wallace et al+, 1999); this form is specific to testis and brain and has been proposed to replace the 64K form during some steps of spermatogenesi...…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, affinity of CstF for the U͞GU-rich elements, which are highly variable in sequence, defines the efficiency of poly(A) sites by determining the stability of the cleavage complex on the pre-mRNA (22). In mammalian cells, several studies have correlated shifts in the choice of poly(A) sites with quantitative or qualitative variations of CstF-64 (23)(24)(25)(26)(27). In Drosophila, we and others have shown that modulation of su(f) activity in su(f) mutants affects the utilization of alternative poly(A) sites in the f 1 mutation, the Adh͞Adhr locus, and the su(f) gene itself (19,20,28,29).…”
mentioning
confidence: 99%
“…The nature of the highly variable downstream element of the poly(A) site has a considerable impact on ternary complex stability and may therefore contribute to poly(A) site selection. Work by Mann et al (1993) suggests that the modulation of the activity of CstF, the factor responsible for recognition of the downstream element, may play a key role in the regulation of adenovims poly(A) site selection.…”
mentioning
confidence: 99%